Effect of Dual Infection with Eimeria tenella and Subgroup J Avian Leukosis Virus on the Cecal Microbiome in Specific-Pathogen-Free Chicks - Cui, Ning; Wang, Xiuzhen; Wang, Qi; Li, Hongmei; Wang, Fangkun; Zhao, Xiaomin (Frontiers in Veterinary Science, 2017)
Understanding gut microflora alterations associated with gut parasites and other pathogens that drive these alterations may help to promote the understanding intestinal flora's role in multiple infected individuals. This study examined the effects of dual infection with Eimeria tenella and subgroup J avian leukosis virus (ALV-J) on the chick cecal microbiome. Specific-pathogen-free (SPF) chicks were infected with either ALV-J strain NX0101 at 1 d of age, or E. tenella at 14 d of age, another group was infected with both pathogens. Cecal contents from chicks were extracted at the 21 d of age and examined using 16S rRNA genes Illumina sequencing. A genus-level opportunistic pathogen enrichment and a decrease in possible resident probiotics were observed in response to all infection groups. Of note, E. tenella mainly induced a sharp decrease in the richness and diversity of cecal microflora from infected chicks because of the serious E. tenella-induced damage to intestinal tissues. ALV-J infection led to structural changes and increased the richness and diversity of the cecal microflora. As for E. tenella and ALV-J dual infected chicks, a marked enrichment of opportunistic pathogens in addition to some other bacteria that may play a role involving cecal microbiota carbohydrate transport and metabolic functions were also found compared to single pathogen-infected chicks. Overall, this study provides valuable insights into the SPF chick cecal microbial community, the modulations of this community in response to different pathogenic infections of single or dual infections, and the interactions between different pathogens and hosts from the perspective of intestinal microflora.